Chocolate milk and endurance exercise recovery: protein balance, glycogen, and performance. - Lunn, William R; Pasiakos, Stefan M; Colletto, Megan R; Karfonta, Kirstin E; Carbone, John W; Anderson, Jeffrey M; Rodriguez, Nancy R (Medicine and science in sports and exercise, 2012)
Purpose: This study examined effects of fat-free chocolate milk (MILK) consumption on kinetic and cellular markers of protein turnover, muscle glycogen, and performance during recovery from endurance exercise. Methods: Male runners participated in two trials separated by 1 wk and consumed either MILK or a nonnitrogenous isocaloric carbohydrate (CHO) control beverage (CON) after a 45-min run at 65% of V̇O 2peak. Postexercise muscle protein fractional synthetic rate (FSR) and whole-body protein turnover were determined during 3 h of recovery using muscle biopsies and primed constant infusions of L-[ring-H5]phenylalanine and L-[1-C]leucine, respectively. Phosphorylation of translational signaling proteins and activity of proteolytic molecules were determined using Western blotting and enzymatic activity assays. Muscle glycogen was quantified, and treadmill time to exhaustion was determined after the recovery period. Results: Consuming MILK after exercise resulted in higher mixed muscle FSR with lower whole-body proteolysis and synthesis compared with CON (P ≤ 0.05). Phosphorylation of eIF4E-BP1 and FOXO3a was higher for MILK (P < 0.01), whereas Akt phosphorylation was lower during recovery regardless of dietary treatment (P < 0.05). Enzymatic activity assays indicated lower caspase-3 activity during recovery for MILK (P < 0.01) and higher 26S proteasome activity for CON (P < 0.01). Muscle glycogen was not affected by either dietary treatment; however, time to exhaustion was greater for MILK than for CON (P < 0.05). Conclusions: The effects of consumption of MILK after endurance exercise on FSR, signaling molecules of skeletal muscle protein turnover, leucine kinetics, and performance measures suggest unique benefits of milk compared with a CHO-only beverage. © 2012 by the American College of Sports Medicine.
Keywords: *Athletic Performance/ph [Physiology]; *Cacao/me [Metabolism]; *Milk/me [Metabolism]; *Muscle Proteins/bi [Biosynthesis]; *Physical Endurance/ph [Physiology]; ATP dependent 26S protease; Adaptor Proteins, Signal Transducing; Adaptor Proteins, Signal Transducing/me [Metabolism]; Adult; Animals; Athletic Performance; Cacao; Cell Cycle Proteins; Dietary Carbohydrates; Dietary Carbohydrates/me [Metabolism]; EIF4EBP1 protein, human; FOXO3 protein, human; Forkhead Box Protein O3; Forkhead Transcription Factors; Forkhead Transcription Factors/me [Metabolism]; Glycogen; Glycogen/an [Analysis]; Heart Rate; Heart Rate/ph [Physiology]; Humans; Male; Milk; Muscle Proteins; Muscle, Skeletal; Muscle, Skeletal/ch [Chemistry]; Muscle, Skeletal/me [Metabolism]; Muscle, Skeletal/ph [Physiology]; Oxygen Consumption; Oxygen Consumption/ph [Physiology]; Phosphoproteins; Phosphoproteins/me [Metabolism]; Phosphorylation; Physical Endurance; Proteasome Endopeptidase Complex; Proteasome Endopeptidase Complex/an [Analysis]; Protein synthesis; Proto-Oncogene Proteins c-akt; Proto-Oncogene Proteins c-akt/me [Metabolism]; Young Adult; adult; animal; article; athletic performance; biosynthesis; cacao; carbohydrate diet; chemistry; dept.hms; endurance; forkhead transcription factor; glycogen; heart rate; human; intracellular signaling; leucine kinetics; male; metabolism; milk; muscle glycogen; muscle protein; oxygen consumption; peer-reviewed; phosphoprotein; phosphorylation; physiology; proteasome; protein kinase B; proteolysis; signal transducing adaptor protein; skeletal muscle; time to exhaustion

Physical activity strategies for improved cognition: the mind/body connection - Fede, Marybeth H (Strategies: a journal for physical and sport educators, 2012)
Keywords: dept.hms